MCSE designing a Windows server 2003 active directory and network : infrastructure exam 70-297 - Barber, Brian (Rockland, MA : Syngress Pub., 2004)
MCSE Designing a Microsoft Windows Server 2003 Active Directory and Network Infrastructure (Exam 70-297) Study Guide and DVD Training System is a one-of-a-kind integration of text, DVD-quality instructor led training, and Web-based exam simulation and remediation. This system gives readers 100% coverage of the official Microsoft exam objectives plus test preparation software for the edge needed to pass the exam on your first try. * DVD Provides a "Virtual Classroom": Get the benefits of instructor led training at a fraction of the cost and hassle. * Guaranteed Coverage of All Exam Objectives: If the topic is listed in Microsoft's exam objectives, it is covered here. * Fully Integrated Learning: This system includes a study guide, DVD training, and Web-based practice exams.
Includes index.
Includes Web-based training.
Keywords: Microsoft Windows (Computer file).; Microsoft software -- Examinations -- Study guides; Directory services (Computer network technology) -- Examinations -- Study guides; Electronic data processing personnel -- Examinations -- Study guides; Electronic books